2011
DOI: 10.1159/000323879
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria as Trigger for Chronic Gastrointestinal Disorders

Abstract: Apart from acute infections, microorganisms may also induce or perpetuate chronic inflammatory diseases and reversible or irreversible proliferation of various cells in the gastrointestinal tract (the extreme being adenocarcinoma and lymphoma). Helicobacter pylori is not only involved in the pathogenesis of lymphoma and gastric adenocarcinoma. The steps and mechanisms of the carcinogenic process involve host predisposition, environmental factors, and strain virulence. The steps of lymphoma genesis include chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 77 publications
0
21
0
2
Order By: Relevance
“…The GF animal model represents a fundamental tool to explore and elucidate the interaction between the host and its microbiota. In the absence of microbiota, GF animals are generally more susceptible to microbial infections (Fagundes et al, 2012); however, GF status can ensure a higher resistance to some other pathological conditions (generally involving inflammation), in which the indigenous microbiota acts as a trigger to induce the disease (Marteau & Chaput, 2011;Xavier & Podolsky, 2007). Fagundes et al (2012) demonstrated that GF mice did not survive a bacterial lung infection due to their inability to effectively process an appropriate inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…The GF animal model represents a fundamental tool to explore and elucidate the interaction between the host and its microbiota. In the absence of microbiota, GF animals are generally more susceptible to microbial infections (Fagundes et al, 2012); however, GF status can ensure a higher resistance to some other pathological conditions (generally involving inflammation), in which the indigenous microbiota acts as a trigger to induce the disease (Marteau & Chaput, 2011;Xavier & Podolsky, 2007). Fagundes et al (2012) demonstrated that GF mice did not survive a bacterial lung infection due to their inability to effectively process an appropriate inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…These pathogens are able to cause acute or chronic damage to the host (95,96) or are linked to (postinfectious) complications (97)(98)(99)(100)(101)(102)(103)(104)(105)(106)(107).…”
Section: Cas9 As a Regulator Of Bacterial Virulencementioning
confidence: 99%
“…Diagnosis of a persistent infection can be difficult, as signs are not always obvious. A prolonged persistent infection can cause a chronic inflammatory state, which could lead to complications or even precipitation of certain diseases in susceptible hosts (2)(3)(4). It may also cause organ damage, which eventually weakens the immune system, leading to symptomatic infection.…”
mentioning
confidence: 99%